Estimulação elétrica neuromuscular na reabilitação da disfagia orofaríngea neurogênica - Cola, Paula Cristina [UNESP]; Dantas, Roberto Oliveira; Silva, Roberta Gonçalves da [UNESP] (My University, 2012)
Objective. To present an overview of the literature about the efficacy of neuromuscular electrical stimulation (NMES) in the rehabilitation of neurogenic oropharyngeal dysphagia and to compare methods of therapy in stroke. Method. An extensive bibliographic survey of several databases (Medline, Scielo Brazil, Chile and Spain and Lilacs) was performed using the following keywords: deglutition disorders, therapy, electrical stimulation, pharynx and stroke between 1990 and 2011. Results. The articles reported the use of NMES in heterogeneous population; there is no consensus thus far about the method used during the NMES and about its rehabilitation efficacy in neurogenic oropharyngeal dysphagia. Conclusions. After this study, we concluded that further investigations are necessary with homogeneous groups of patients with neurogenic dysphagia, discussing the proposition of a specific NMES protocol for the rehabilitation of neurogenic oropharyngeal dysphagia.
Neuromuscular electrical stimulation in rehabilitation of neurogenic oropharyngeal dysphagia
Keywords: Deglutition Disorders; Electric Stimulation Therapy; Stroke; dysphagia; health survey; human; intermethod comparison; medical literature; Medline; neurogenic oropharyngeal dysphagia; neuromuscular electrical stimulation; pharynx; review; stroke; systematic review; therapy effect